An audit of culture-proven neonatal sepsis at a tertiary hospital in South Africa: a retrospective review - Mapele, Apamu Jacques (My University, 2021)
Background: Approximately one third of under five deaths occur during the neonatal period. Neonatal sepsis (NNS) is major cause of morbidity and mortality. Therefore, sick neonates with signs and symptoms of possible sepsis are provided with early empiric antibiotic therapy from birth. The choice of empiric antibiotic therapy is based on surveillance data of antimicrobial sensitivity patterns in culture isolates. Neonatal pathogens vary not only between different neonatal units but also over time in the same unit. The antibiotic susceptibility patterns of pathogens also change with time and with the emergence of multidrug resistant organisms. The aim of this study were to describe clinical characteristics of neonates in a tertiary referral centre in Gauteng South Africa with culture confirmed blood stream infections as well as the causative organisms and their antimicrobial susceptibility patterns. This information will be used as part of Charlotte Maxeke Johannesburg Academic hospital (CMJAH) neonatal unit antimicrobial stewardship and guide empiric antibiotic therapy. Methods: This was a descriptive retrospective study from January 2018 to June 2019. The clinical data of neonates with confirmed blood stream culture, and the susceptibility profile of organisms were reviewed. Results: There were 386 neonates with positive blood stream culture, which represent a culture confirmed NNS incidence of 15.6 per 100 admissions. Late onset neonatal sepsis (LONS) represented the majority of NNS, 12.3 per 100 admissions (n=304). The commonly identified organism overall was Coagulase-negative Staphylococcus (CONS) (45.9%), followed by Acinetobacter baumannii (11.7%), Staphylococcus aureus (10.4%), Klebsiella pneumoniae (9.3%) and Escherichia coli (4.1%). The majority of Staphylococcus aureus, Klebsiella pneumoniae, and Escherichia coli were respectively methicillin-resistant Staphylococcus aureus(MRSA) (87.5%), extended spectrum beta-lactamase (ESBL) Klebsiella pneumoniae (88.9%), and ESBL Escherichia coli(56.3%). Candida parapsilosis (2.8%) was the predominant fungus, susceptible to amphotericin B. Conclusion: NNS is a major problem in neonatal unit of CMJAH. The antibiotic resistant organisms are common. The commonly identified organism overall was CONS, followed by Acinetobacter baumannii, Staphylococcus aureus, Klebsiella pneumoniae and Escherichia coli. The suitable empiric antibiotic for early onset neonatal sepsis (EONS) would be ampicillin and amikacin while LONS would be covered by vancomycin and meropenem
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the Master of Medicine in Paediatrics, 2021